TREATMENT OF OLD PEOPLE ACCORDING TO AGE SPECIALTIES - N.B.Nurov (Scholar Express Journal, 2021)
Due to the fact that in recent years the proportion of elderly and senile people in developed countries has been steadily growing, the interest of specialists in the health and quality of life of elderly people has increased significantly (Kairbekov A.K., 2009; Baysultanova A.Sh., 2009; Turebekov D.K. et al., 2009). Anatomical and topographic features of the structure of both jaws suggest that the best department for the effective installation of a sufficient number of implants in this group of patients is the frontal section of the upper and lower jaws, where there is always a sufficient amount of bone tissue for bicortical and intercortical installation of 4-6 implants of the appropriate diameter and length (Botabaev K.A., 2010).
Keywords: Elderly And Senile People; Anatomical and topographic features